EIB Working Paper 2021/04 - Aggregate productivity slowdown in Europe New evidence from corporate balance sheets - Wolski, Marcin (European Investment Bank, 2021)
Using firm balance sheet data, this paper shows the impact of credit constraints on allocative efficiency and productivity growth. Allocative efficiency is the extent to which resources, including labour, are distributed to firms with the highest growth prospects, or "stuck" in less productive firms. This paper uses firm balance sheet data to analyse the role of financial constraints in the relatively muted post-crisis rebound in productivity in 2014-17, compared to previous upturns in Europe. It shows that the level of financial leverage played an important role in explaining the change in aggregate productivity growth in Europe between 2004 and 2017. Focusing on Northern and Western Europe, it also shows that the productivity potential could not be fully exploited due to constraints on access to credit. It estimates that reducing collateral bottlenecks could more than double the effectiveness of financial leverage in spurring productivity growth in this region between 2014-17.